OF CHEMICAL EXPERIMENTS IN THE PROCESS OF CHEMISTRY TEACHING (World Bulletin of Social Sciences, 2024)
This article examines the importance and effectiveness of using chemical experiments in the process of teaching organic chemistry in general secondary schools. The article provides information on how the use of experiments contributes to a deeper understanding of the basic principles of organic chemistry by students. The analysis of literature sources and studies was carried out, and the effectiveness of using chemical experiments in increasing students' interest and enthusiasm for learning organic chemistry was determined
Keywords: Morden technology; teaching methodology; alcohol